2005
DOI: 10.1016/j.femsle.2005.04.037
|View full text |Cite
|
Sign up to set email alerts
|

Fungi isolated from contaminated baled grass silage on farms in the Irish Midlands

Abstract: The incidence of fungal growth on baled grass silage was recorded on 35 farms in the Irish Midlands in 2003. Fungal colonies were visible on 58 of 64 bales examined and the number of colonies per bale ranged from 1 to 12. On average, 5% of bale surface areas were affected. The fungus most prevalent on bales was Penicillium roqueforti, present on 86% of bales and representing 52% of all isolates. Other moulds isolated were Penicillium paneum, Geotrichum, Fusarium and mucoraceous species. Schizophyllum commune w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
43
1
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 14 publications
(18 reference statements)
6
43
1
3
Order By: Relevance
“…The trend towards higher numerical values for the Penicillium mycotoxins MPA and Roq. C within baled silages agrees with the high incidence of P. roqueforti identified in baled silages by O'Brien et al, (2005), and suggests that excess air had penetrated the plastic stretch-film barrier in which these bales were wrapped. Baled silage is usually wrapped in a thinner layer of plastic film to exclude air and has a higher silage surface area to total volume ratio than pit silage .…”
Section: Mycotoxins Profiles In Baled and Pit Silagessupporting
confidence: 71%
See 1 more Smart Citation
“…The trend towards higher numerical values for the Penicillium mycotoxins MPA and Roq. C within baled silages agrees with the high incidence of P. roqueforti identified in baled silages by O'Brien et al, (2005), and suggests that excess air had penetrated the plastic stretch-film barrier in which these bales were wrapped. Baled silage is usually wrapped in a thinner layer of plastic film to exclude air and has a higher silage surface area to total volume ratio than pit silage .…”
Section: Mycotoxins Profiles In Baled and Pit Silagessupporting
confidence: 71%
“…The preservation of these silages depends on achieving strictly anaerobic conditions within the silo or bale to inhibit the aerobic activity of fungi and bacteria. However, a previous survey of baled silage in Ireland identified that 91% of the bales contained visible fungal mould growth (O'Brien, et al, 2005), including Fusarium and Penicillium, indicating that adequately anaerobic conditions did not prevail. These moulds are toxigenic and can produce secondary fungal metabolites, namely mycotoxins.…”
Section: Introductionmentioning
confidence: 94%
“…The third source of mycotoxins in the diet of dairy cows results from the consumption of preserved feeding stuffs such as silage, hay, and straw (O'Brien et al 2005;Mansfield and Kuldau 2007). Particularly after a longer storage period, silage can be spoiled by a variety of fungal species, which are acid-tolerant and micro-aerobe.…”
Section: Mycotoxins In Feeds For Dairy Cattlementioning
confidence: 99%
“…Furthermore, mould growth decreases the nutritive value of the silage even more and also lowers its palatability (DiConstanzo et al 1995, Wilkinson 2005. Mould species that regularly have been isolated from silage belong to the genera Penicillium, Aspergillus, Mucor, Byssochlamys, Fusarium, Alternaria, Geotrichum, Monascus, Paecilomyces and Trichoderma (Nout et al 1993, Auerbach et al 1998, O'Brien et al 2005, Mansfield et al 2008, Declerck et al 2009). Fusarium, Aspergillus and Penicillium are the most important mycotoxin producing mould genera.…”
Section: Introductionmentioning
confidence: 99%